2022
DOI: 10.47197/retos.v46.91541
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de la influencia de las variables situacionales en el fútbol profesional (Analysis of the influece of situational variables in professional soccer)

Abstract: El conocimiento objetivo de los indicadores de juego que ocurren durante la competición permite a los entrenadores realizar planes de entrenamiento ajustados a las necesidades competitivas. El propósito de este trabajo fue analizar la influencia de la localización, el efecto de marcar primero y la calidad del oponente parcial y final en el resultado, en función del momento de la temporada en una liga profesional de fútbol. Para ello, se analizaron 114 jornadas de liga de la Primera División Española de Fútbol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
3
0
3
Order By: Relevance
“…Data also showed that U23 teams of lower or similar quality scored more often during the match, further substantiating our supposition that the competitive balance increases with age. Regardless of situational circumstances, it is plausible to assume that U23 lowerranked teams might be technically, tactically, physically, and mentally capable of keeping the match open (tied leagues (Armatas, et al, 2009;Fernández-Cortés, et al, 2022;Lago-Peñas, et al, 2016;Martínez & González-García, 2019). At the very least, these findings challenge the common belief that the last 15 minutes (plus additional time) is the most critical phase of the game (Leite, 2013;Njororai, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data also showed that U23 teams of lower or similar quality scored more often during the match, further substantiating our supposition that the competitive balance increases with age. Regardless of situational circumstances, it is plausible to assume that U23 lowerranked teams might be technically, tactically, physically, and mentally capable of keeping the match open (tied leagues (Armatas, et al, 2009;Fernández-Cortés, et al, 2022;Lago-Peñas, et al, 2016;Martínez & González-García, 2019). At the very least, these findings challenge the common belief that the last 15 minutes (plus additional time) is the most critical phase of the game (Leite, 2013;Njororai, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that home teams scored more goals in the early stages of matches, which tend to be more critical for the match outcome (Caballero, et al, 2017;Carmo, et al, 2021;Martínez & González-García, 2019), and that is when players experience the most demanding passages of play (Oliva-Lozano, et al, 2021). Recent studies have indicated that home teams are more likely to score goals and win matches irrespective of their age group or competitive level (amateur, semi-professional, and professional), a phenomenon known as the "home advantage effect" (Almeida & Volossovitch, 2017;Fernández-Cortés, et al, 2022;Staufenbiel, et al, 2018). As expected, the number of home goals surpassed the away goals in the analysed age groups (U17, 51%; U19, 54.4%; U23, 53%); however, the extent to which the home advantage effect increases with age (Staufenbiel, et al, 2018) should be scrutinised in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speed, agility, balance, and coordination (commonly abbreviated as SABC) are critical skill elements in modern soccer Sulistiyono et al, 2022). SABC can assist young soccer players in improving their reaction speed to on-field situations, enhancing more accurate and effective ball control, and making more precise and timely passing decisions (Robertson et al, 2015), It also helps in increasing the ability to create goal-scoring opportunities and enhances the skill of running and dribbling at high speeds, enabling them to attack the opponent's defense more effectively (Fernández-Cortés et al, 2022;Gaudion et al, 2017;Chalmers & Magarey, 016;de Macedo et al, 2022). Speed is an individual's ability to perform continuous movements in a short amount of time (Wang & Shi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Inserido na análise de desempenho, encontra-se a análise de jogo, que por sua vez tem como principal objetivo compreender as características e singularidades dos padrões comportamentais de equipes em treinamento e competições (MARCELINO, SAMPAIO, MESQUITA; 2011). Dentro da análise de jogo, identificam-se variáveis contextuais que são capazes de influenciar no desempenho físico, tático e técnico da equipe (SARMENTO, BRADLEY, TRAVASSOS;AQUINO et al, 2017FERNÁNDEZ-CORTÉS et al, 2022. Tais variáveis podem ser consideradas pela comissão técnica ao definir estratégias e na modelação tática ao enfrentar uma equipe específica (SARMENTO et al, 2014).…”
Section: Contextuaizaçãounclassified